The souls of Black folk - William Edward Burghart Du Bois (Gramercy Books, 1994)
The book exposses with brutal honesty and poetic indignation the plights of former slaves, their children, and their grandchildren at the beginning of the twentieth century. It discusses the failure of Reconstruction and of the Freeman's Bureau; the scarcity of educational opportunities for black children; the poverty and lack of motivation of many rural blacks; and the conditions and attitudes of both whites and blacks in the South at the time of the book's publication 1903